Comparative Analysis of FABA Waste Composition in Various Coal-Fired Power Plant Industries in Several Countries and Indonesia: A Review - Putra, M. Sulthon Nurharmansyah; Prasojo, Agus Eko; Budiman, Anggito; Anty, Mentari Zikri; Hasnowo, Lutfi Aditya (Indonesian Scholar Society, 2024)
Fly Ash and Bottom Ash (FABA) is the waste from burning coal in coal-fired power plants and consists of chemical compounds, such as SiO₂, Al₂O₃, Fe₂O₃, and CaO. This waste poses an environmental challenge and an opportunity for the construction industry. This study conducted a comparative analysis of the composition of FABA from several coal-fired power plants in Indonesia and other countries, such as Thailand, China, Malaysia, France, Italy, and Portugal. In particular, this study assessed the XRF data from several other references. The XRF test data showed significant variations in the FABA content, influenced by coal type, combustion method, and emission management technology. The high SiO₂ content in the Cirebon and Teluk Sirih coal-fired power plants showed potential for pozzolanic applications. Meanwhile, the high Fe₂O₃ in Tanjung Enim and Sudimoro had the potential for metallurgical applications. In addition, the high CaO content of Teluk Sirih allowed its use in lime production and soil stabilization. However, high levels of SO₃, especially in Cirebon, required more attention in processing because of its impact on concrete quality and environmental pollution. With proper processing, FABA could be a valuable resource in various industries, reducing reliance on natural raw materials. This study highlighted the potential for the sustainable use of FABA and proposed management measures to address environmental challenges. The optimal use of FABA reduced negative environmental impacts and opened up significant economic opportunities, supporting the circular economy in the energy and construction sectors.